Fully Integrated Chen Chaotic Oscillation System - Ziyi Ouyang; Jie Jin; Fei Yu; Long Chen; Lei Ding (Discrete Dynamics in Nature and Society)
A fully integrated Chen chaotic oscillation system using operational amplifiers (OAs) and multipliers is designed and verified in this paper. Unlike the conventional breadboard-based Chen chaotic system using off-the-shelf discrete components, the fully integrated Chen chaotic oscillation circuit presented in this paper is realized using GlobalFoundries’ 0.18 μm CMOS 1P6M process, and all the circuit components are integrated in a chip. The fully integrated Chen chaotic oscillation system is verified using Cadence IC Design Tools, and the post-layout simulation results indicate that the presented integrated Chen chaotic oscillation system only consumes 148 mW from ± 2.5 V supply voltage, and its chip area is 6.15 mm2.